Bronchiectasis and deteriorating lung function in agammaglobulinaemia despite immunoglobulin replacement therapy. (3rd November 2017) - Stubbs, A.; Bangs, C.; Shillitoe, B.; Edgar, J. D.; Burns, S. O.; Thomas, M.; Alachkar, H.; Buckland, M.; McDermott, E.; Arumugakani, G.; Jolles, M. S.; Herriot, R.; et al.
Summary: Immunoglobulin replacement therapy enhances survival and reduces infection risk in patients with agammaglobulinaemia. We hypothesized that despite regular immunoglobulin therapy, some patients will experience ongoing respiratory infections and develop progressive bronchiectasis with deteriorating lung function. One hundred and thirty‐nine (70%) of 199 patients aged 1–80 years from nine cities in the United Kingdom with agammaglobulinaemia currently listed on the UK Primary Immune Deficiency (UKPID) registry were recruited into this retrospective case study and their clinical and laboratory features analysed; 94% were male, 78% of whom had Bruton tyrosine kinase (BTK ) gene mutations. All patients were on immunoglobulin replacement therapy and 52% had commenced therapy by the time they were 2 years old. Sixty per cent were also taking prophylactic oral antibiotics; 56% of patients had radiological evidence of bronchiectasis, which developed between the ages of 7 and 45 years. Multivariate analysis showed that three factors were associated significantly with bronchiectasis: reaching 18 years old [relative risk (RR) = 14·2, 95% confidence interval (CI) = 2·7–74·6], history of pneumonia (RR = 3·9, 95% CI = 1·1–13·8) and intravenous immunoglobulin (IVIG) rather than subcutaneous immunoglobulin (SCIG) = (RR = 3·5, 95% CI = 1·2–10·1), while starting immunoglobulin replacement after reaching 2 years of age, gender and recent serum IgG concentration were not associated significantly. Independent of age, patients with bronchiectasis had significantly poorer lung function [predicted forced expiratory volume in 1 s 74% (50–91)] than those without this complication [92% (84–101)] ( P  < 0·001). We conclude that despite immunoglobulin replacement therapy, many patients with agammaglobulinaemia can develop chronic lung disease and progressive impairment of lung function. Abstract : We hypothesized that some patients treated for agammaglobulinemia with regular immunoglobulin therapy will develop progressive bronchiectasis with deteriorating lung function. Of 139 patients aged 1 to 80 years with agammaglobulinemia recruited from nine UK cities into this retrospective case study, 56% had radiological evidence of bronchiectasis and reduced lung function. We conclude that despite immunoglobulin replacement therapy, many patients with agammaglobulinemia develop chronic lung disease and progressive impairment of lung function.